Japanese Encephalitis Viruses from Bats in Yunnan, China - Jing-Lin Wang; Xiao-Ling Pan; Hai-Lin Zhang; Shi-Hong Fu; Huan-Yu Wang; Qing Tang; Lin-Fa Wang; Guo-Dong Liang (Emerging Infectious Diseases, 2009)
Genome sequencing and virulence studies of 2 Japanese encephalitis viruses (JEVs) from bats in Yunnan, China, showed a close relationship with JEVs isolated from mosquitoes and humans in the same region over 2 decades. These results indicate that bats may play a role in human Japanese encephalitis outbreaks in this region.